Optimal red:blue ratio of full spectrum LEDs for hydroponic pakchoi cultivation in plant factory - Li, Yunong; Liu, Nan; Ji, Fang; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2022)
Pakchoi, a popular leafy vegetable in China, is expected to be planted in plant factories with artificial lighting (PFALs). In order to examine the effects of different red and blue light ratios (R:B ratio) on growth, photosynthesis, and absorption spectrum of plant leaves, and to analyze the energy use efficiency, the pakchoi (Brassica Chinensis L. cv. Xiazhijiao) was cultivated hydroponically under white LEDs with R:B ratios of 0.9 (L0.9) and 1.8 (L1.8), white plus red LEDs with R:B ratios of 2.7 (L2.7) and 4.0 (L4.0) for 40 d, respectively. The results showed that the leaf length and width were significantly greater in the L0.9 treatment than in other treatments, and the dry weight per plant increased by over 33% when R:B ratio decreased from 4.0 to 0.9. The net photosynthesis rates of pakchoi leaves ranged from 9.2 to 9.6 μmol/(m2·s) under different lighting conditions, which had no significant difference. The biggest difference in the spectrum absorptance of pakchoi leaves was expressed in green light waveband, and the highest absorption of plant leaves was under L0.9 and L1.8 treatments. The light energy use efficiency (LUE), photon yield (PY), and energy yield (EY) in L0.9 were over 25% higher than that in the other treatments, while there was no significant difference in the electrical energy use efficiency (EUE). In conclusion, an optimal light quality to cultivate pakchoi in PFALs was the white LEDs with R:B ratio of 0.9, and this finding could provide a promising lighting environment to hydroponic pakchoi yield and energy use efficiency.Keywords: pakchoi, R:B ratio, yield, absorption spectrum, energy use efficiencyDOI: 10.25165/j.ijabe.20221503.7362Citation: Li Y N, Liu N, Ji F, He D X. Optimal red:blue ratio of full spectrum LEDs for hydroponic pakchoi cultivation in plant factory. Int J Agric & Biol Eng, 2022; 15(3): 72–77.